TRANSFORMASI PENGETAHUAN TAK TERTULIS: PENDEKATAN METALITERASI DALAM DOKUMENTASI WARISAN BUDAYA LISAN MINANGKABAU - Satria, Ridho Yogi; Zalmi, Fadhila Nurul Husna Zalmi (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2025)
The oral cultural heritage of the Minangkabau represents a form of tacit knowledge rich in values, yet vulnerable to extinction due to limited systematic documentation and shifting communication patterns among younger generations. Within the field of library and information science, the preservation of such local knowledge demands a literacy strategy that goes beyond technical skills to include critical, collaborative, and ethical thinking, as promoted by the metaliteracy framework. This study aims to explore the transformation of tacit knowledge through the documentation of Minangkabau oral traditions using a metaliteracy approach as a strategy for preserving cultural information. The research employs a qualitative methodology with an ethnographic design, involving in-depth interviews, participatory observation, and content analysis of oral expressions such as kaba, pantun, and pepatah-petitih. The findings indicate that integrating metaliteracy into the documentation process not only enhances the quality of cultural information management but also empowers local communities to serve as both producers and curators of knowledge. Collaborative and reflective documentation practices enable oral traditions to be transformed into accessible information resources across generations and media platforms. The study concludes that the metaliteracy approach plays a crucial role in fostering adaptive and inclusive documentation practices in library and information science, particularly in preserving local knowledge. It recommends strengthening community-based information literacy capacities as a sustainable strategy for maintaining the continuity of Minangkabau oral heritage.